2013
DOI: 10.2175/106143012x13373575831394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticles and Antibiotics on Antibiotic Resistance Genes in Anaerobic Digestion

Abstract: Water resource recovery facilities have been described as creating breeding ground conditions for the selection, transfer, and dissemination of antibiotic resistance genes (ARGs) among various bacteria. The objective of this study was to determine the effect of direct addition of antibiotic and silver nanoparticles (Ag NPs, or nanosilver) on the occurrence of ARGs in thermophilic anaerobic digesters. Test thermophilic digesters were amended with environmentally-relevant concentrations of Ag NP (0.01, 0.1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 52 publications
5
38
0
Order By: Relevance
“…As oxygen was absent in their study, no released silver ion was detected, which was recognized as the main reason for Ag-NPs showing no inhibitory effect on methanogenic activities. Similar result was reported by Miller et al (2012). Nevertheless, when sewage sludge was treated in the landfill bioreactors in the presence of Ag-NPs, the methanogenesis was adversely influenced (Yang et al, 2012b), and the toxicity of Ag-NPs was observed to be higher than its counterpart silver ion (Yang et al, 2013b(Yang et al, , 2013c.…”
Section: Impacts Of Nps On Wastewater Treatment and Sewage Sludge Digsupporting
confidence: 85%
“…As oxygen was absent in their study, no released silver ion was detected, which was recognized as the main reason for Ag-NPs showing no inhibitory effect on methanogenic activities. Similar result was reported by Miller et al (2012). Nevertheless, when sewage sludge was treated in the landfill bioreactors in the presence of Ag-NPs, the methanogenesis was adversely influenced (Yang et al, 2012b), and the toxicity of Ag-NPs was observed to be higher than its counterpart silver ion (Yang et al, 2013b(Yang et al, , 2013c.…”
Section: Impacts Of Nps On Wastewater Treatment and Sewage Sludge Digsupporting
confidence: 85%
“…Ultrasound generated the shear stress induced by cavitation while high temperature led to denaturation and loss of function of enzymes, nucleic acids, organelles and other cellular structures (Neumann et al, 2018). Microwave irradiation, UV, or nanoparticle were also reported to successfully improve the AD performance, achieving higher inactivation rate of fecal coliforms than single AD (Hong et al, 2006;Neto et al, 2006;Miller et al, 2013). The biotechnological development was less reported to integrate with AD compared to physiochemical technologies.…”
Section: Refs Mesophilic Thermophilicmentioning
confidence: 99%
“…16 Triclosan-resistant bacteria exhibiting resistance to other antimicrobials were also found in a wastewater-impacted river. 17 The effect of triclosan on ARGs in anaerobic wastewater communities, where ARGs are abundant, [18][19][20] is poorly understood. Because ARGs are contaminants of concern 21 with negative public health consequences, 22 it is important to understand if triclosan can have an impact on the proliferation of ARGs in anaerobic wastewater communities where triclosan exposure can be high.…”
Section: Introductionmentioning
confidence: 99%